ANALYSIS OF STUDENT SATISFACTION WITH STUDENT MANAGEMENT SERVICES IN THE INFORMATION SYSTEMS STUDY PROGRAM AT PRIMA INDONESIA UNIVERSITY USING THE SERVICE QUALITY (SERVQUAL) METHOD - Wijaya, Malvin Luckianto; Sitompul, Daniel Ryan Hamonangan; Sinurat, Stiven Hamonangan; Rahmad, Julfikar; Fahmi, Mohammad Irfan; Indra, Evta (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The purpose of this research is to analyze the level of student satisfaction with student management services in the Information Systems Study Program at Prima Indonesia University. The method used in this study is the Service Quality method to measure the level of student satisfaction. The results of the research show that the level of student satisfaction with student management services is 4.28 and the Servqual method has good quality in measuring student satisfaction.